Internet-based breastfeeding peer support for breastfeeding parents : An integrative review - Hiito, Elisa (Wiley-Blackwell, 2025)
Aim: To explore what Internet-based breastfeeding peer support offers to breastfeeding parents.
Design: Integrative review.
Data sources and review methods: A systematic literature search was conducted in March 2024 using the following electronic databases: CINAHL, The Cochrane Library, PubMed/MEDLINE and PsycINFO. Database searches yielded 717 results. Two researchers removed the duplicates (n = 256) and screened the remaining titles (n = 461), abstracts (n = 197) and full texts (n = 60) independently. Eventually, 19 studies were included in the review. The chosen studies had qualitative (n = 11), quantitative (n = 6), or mixed methods designs (n = 2) and were published between 2015 and 2024. Qualitative content analysis was conducted.
Results: The main categories were supplying support that is responsive to the needs of parents and belonging to a breastfeeding community. The parents looked for and received breastfeeding support, advice, information, emotional support, reassurance and access to shared experiences from various online breastfeeding peer support groups. The support groups helped them in their breastfeeding decisions, thus making a difference in their breastfeeding experience. The support groups created breastfeeding communities for these parents and they were able to bond with others, feel like they belonged and share experiences. Additionally, these breastfeeding communities helped to normalize various breastfeeding practices.
Conclusion: Breastfeeding peer support groups can offer parents the support and guidance they seek and a sense that they are part of a breastfeeding community. However, it is vital these groups are efficiently moderated to ensure the advice parents receive is evidence-based and the support is encouraging.
Impact: These findings show that well-moderated online breastfeeding peer support can offer parents high-quality support. It is essential for health care professionals to be aware of the various options available in order to recommend high-quality support groups for breastfeeding parents.
Reporting method: PRISMA.
Patient or public contribution: This was an integrative review therefore no patient or public contribution was necessary.